Skype sessions as a way to provide additional oral practice of English university students - García Trejos, Sergio Ramiro; Diaz Pascuas, Rolney Leonardo; Artunduaga Cuellar, Marco Tulio (Colombian Applied Linguistics Journal, 2018)
English teachers frequently find students with a low level of oral proficiency but with a strong desire to put the language they are learning into practice. The lack of opportunities, time, and spaces to use the language both inside and outside the classroom to interact with others makes the situation even more challenging. This article was conducted as part of the final thesis in the master’s degree program in English Didactics from Universidad Surcolombiana, and which aimed at exploring the impact of using Skype as a complementary tool to foster oral production in a group of university students in Neiva, Colombia. Participants included four students from the first level of English with a basic command of the language. Theoretical constructs such the use of Skype in EFL, computer-mediated communication (CMC), social networking, cooperative learning, and oral production in CMC were taken into account. The pedagogical interventions in the study consisted of six Skype video-conferences between a teacher-researcher and the four participants. Data collection included video-conference transcripts, field notes, and students’ journals. The data were analyzed using qualitative methods. Findings evidence that Skype has a positive impact on the EFL context in areas like language learning, social interaction, and emotional influences.